Characterizing population and individual migration patterns among native and restored bighorn sheep (Ovis canadensis). Issue 15 (9th July 2019) - Lowrey, Blake; Proffitt, Kelly M.; McWhirter, Douglas E.; White, Patrick J.; Courtemanch, Alyson B.; Dewey, Sarah R.; Miyasaki, Hollie M.; Monteith, Kevin L.; Mao, Julie S.; Grigg, Jamin L.; Butler, Carson J.; Lula, Ethan S.; et al.
Abstract: Migration evolved as a behavior to enhance fitness through exploiting spatially and temporally variable resources and avoiding predation or other threats. Globally, landscape alterations have resulted in declines to migratory populations across taxa. Given the long time periods over which migrations evolved in native systems, it is unlikely that restored populations embody the same migratory complexity that existed before population reductions or regional extirpation. We used GPS location data collected from 209 female bighorn sheep ( Ovis canadensis ) to characterize population and individual migration patterns along elevation and geographic continuums for 18 populations of bighorn sheep with different management histories (i.e., restored, augmented, and native) across the western United States. Individuals with resident behaviors were present in all management histories. Elevational migrations were the most common population‐level migratory behavior. There were notable differences in the degree of individual variation within a population across the three management histories. Relative to native populations, restored and augmented populations had less variation among individuals with respect to elevation and geographic migration distances. Differences in migratory behavior were most pronounced for geographic distances, where the majority of native populations had a range of variation that was 2–4 times greater than restored or augmented populations. Synthesis and applications . Migrations within native populations include a variety of patterns that translocation efforts have not been able to fully recreate within restored and augmented populations. Theoretical and empirical research has highlighted the benefits of migratory diversity in promoting resilience and population stability. Limited migratory diversity may serve as an additional factor limiting demographic performance and range expansion. We suggest preserving native systems with intact migratory portfolios and a more nuanced approach to restoration and augmentation in which source populations are identified based on a suite of criteria that includes matching migratory patterns of source populations with local landscape attributes. Abstract : We used GPS location data collected from 209 female bighorn sheep ( Ovis canadensis ) to characterize population and individual migration patterns along elevation and geographic continuums for 18 populations with different management histories (i.e., restored, augmented, and native) across the western United States. Differences in migratory behavior were most pronounced for geographic distances, where most native populations had a range of variation that was 2–4 times greater than restored or augmented populations.